Pengaruh Motivasi Dan Disiplin Terhadap Kinerja Guru - Yulius Lende; Erniati Lende; Arsensius Fandi; Antonius Umbu Tawil; Norliana Kaka; Ardianus Ambe Kasa (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This research aims to analyze the influence of motivation and discipline on teacher performance in secondary schools. Motivation and discipline are two important factors that can influence teacher work effectiveness and productivity. This research uses a quantitative method with a survey approach, where data is collected through questionnaires filled out by a number of teachers. The results of data analysis show that both motivation and discipline have a significant influence on teacher performance. High motivation and strict discipline contribute positively to increased performance. These findings show the importance of effective management of motivation and discipline to improve the quality of education in schools.